ANALISIS REVITALISASI PASAR TRADISIONAL PADA PASAR BATUMARTA DALAM PERSPEKTIF EKONOMI ISLAM - Sayu Mainingsih (Al-Iqtishad: Jurnal Ekonomi Syariah, 2023)
Markets are the focal point of local area monetary action which can be arranged into conventional business sectors and current business sectors. The presence of customary business sectors is one of the significant areas that upholds individuals' economy, where the interests of little individuals to the upper working class are upheld. The negative picture of customary business sectors which is inseparable from poor actual parts of structures and market the executives is the justification for why conventional business sectors should be renewed so they can constantly work and contend with current business sectors. The plan of this examination issue is the manner by which the conventional market rejuvenation program at Batumarta Market is done from an Islamic financial point of view. This sort of examination is field research with information assortment techniques through perception, meetings and documentation. The consequences of this exploration show that the renewal program completed at Batumarta Market has had a positive effect, from the physical and the board perspectives, dealers are fulfilled, however there is a requirement for expanded oversight, guideline and upkeep of the market by the Batumarta Market UPTD.